2015
DOI: 10.5194/tc-9-229-2015
|View full text |Cite
|
Sign up to set email alerts
|

Snow depth mapping in high-alpine catchments using digital photogrammetry

Abstract: Abstract. Information on snow depth and its spatial distribution is crucial for numerous applications in snow and avalanche research as well as in hydrology and ecology. Today, snow depth distributions are usually estimated using point measurements performed by automated weather stations and observers in the field combined with interpolation algorithms. However, these methodologies are not able to capture the high spatial variability of the snow depth distribution present in alpine terrain. Continuous and accu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
155
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(170 citation statements)
references
References 54 publications
12
155
1
2
Order By: Relevance
“…SOCET SET ATE and NGATE (all ADS100 point clouds depend on the same absolute orientation) reveal a larger median height difference of 10-17cm. In relation to the 15cm GSD the ADS100 results are definitely improved compared with the results from 2012 (Bühler 2015a Figures 6 and 7 show a rather consistent deviation pattern. SOCET SET ATE and NGATE show for points 01-04 differences 10-22cm, for PHS the difference varies between 4-8cm, which corresponds to the ADS100 GSD of 15cm and PHS GSD of 3cm.…”
Section: Figure 4 Extracted Point Clouds Around Reference Pointssupporting
confidence: 52%
See 1 more Smart Citation
“…SOCET SET ATE and NGATE (all ADS100 point clouds depend on the same absolute orientation) reveal a larger median height difference of 10-17cm. In relation to the 15cm GSD the ADS100 results are definitely improved compared with the results from 2012 (Bühler 2015a Figures 6 and 7 show a rather consistent deviation pattern. SOCET SET ATE and NGATE show for points 01-04 differences 10-22cm, for PHS the difference varies between 4-8cm, which corresponds to the ADS100 GSD of 15cm and PHS GSD of 3cm.…”
Section: Figure 4 Extracted Point Clouds Around Reference Pointssupporting
confidence: 52%
“…Using operationally available aerial images acquired with the Leica ADS80 in 2012, it could be demonstrated that snow depth measurements with 0.30m RMSE can be achieved in high-alpine catchment areas (Bühler 2015a). Due to the high radiometric resolution of the images (12 bits) and the use of the near infrared band (NIR), images were not saturated over bright, snow-covered areas and required texture could be identified even in shadow areas.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, snow depth is mainly estimated from optical measurements such as photogrammetry (Marti et al, 2016;Bühler et al, 2015) or lidar instruments (Deems et al, 2013); however, the applicability of high-frequency radar instruments is currently discussed (Evans and Kruse, 2014). Snow density could potentially be derived from measurements of the snow water equivalent (Leinss et al, 2015) if data about the snow depth are available.…”
Section: Discussionmentioning
confidence: 99%
“…For example, [48] used 37 measurements over 6900 m 2 (0.5 pt/100 m 2 ), [23] took between 0.04 pt/100 m 2 and 0.11 pt/100 m 2 , and [52] took between 0.04 pt/100 m 2 and 0.2 pt/100 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Remote sensing captures the spatial and temporal patterns of snow and thus overcomes the potential undersampling of point measurements and the long surveys needed for snow courses [16,17]. Existing methods include Terrestrial Laser Scanner (TLS, [7,13,[18][19][20][21][22]), digital photogrammetry [23,24], tachymetry [20], Ground Penetrating Radar (GPR) [25], time-lapse photography [26,27], or satellite-based sensors [16]. Among these alternatives, TLS is the commonest choice in most applications [28].…”
Section: Introductionmentioning
confidence: 99%